Analisis Pengalaman Pengguna Pada Aplikasi TIX ID Menggunakan Metode User Experience Questionnaire - Auliya Noor; Elvin Leander Hadisaputro (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
TIX ID is an online cinema ticket purchase application that plays on a smartphone platform. Where users can buy cinema tickets anywhere and anytime without having to wait in line. The concept of purchasing cinema tickets is integrated with a third party, namely DANA as a digital money concept that is integrated with several large applications such as Bukalapak and Ramayana. This study aims to determine the effect of service quality on TIX ID application users in ordering online cinema tickets. and want to know which user experience suits the user both in terms of comfort, function and customer convenience in using TIX ID supporting applications. This study provides a level of satisfaction through a User Experience Questionnaire (UEQ) which has six assessment aspects including attractiveness, perspicuity, efficiency, dependability, stimulation and novelty. The UEQ questionnaire was distributed to 55 respondents, the results of the UEQ questionnaire showed that respondents had a positive impression of the TIX ID application where the application showed a positive evaluation.